Effectiveness of a Peer-Led Pain Management Program in Relieving Chronic Pain and Enhancing Pain Self-Efficacy Among Older Adults: A Clustered Randomized Controlled Trial - Tse, Mimi M. Y.; Ng, Shamay S. M.; Lee, Paul H.; Bai, Xue; Lo, Raymond; Tang, Shuk Kwan; Chan, Ka Long; Li, Yajie (Frontiers in Medicine, 2021)
Chronic pain is common in nursing home residents, who may have difficulty seeking out pain management strategies. Peer support model show promise as a strategy for managing chronic conditions. This was a clustered randomized controlled trial. A peer-led pain management program was provided for the experimental group. Pain situation, depression, quality of life, non-drug strategies used, and pain knowledge were measured. A total of 262 participants joined the study (146 were allocated as experimental group and 116 as control group). Before our intervention, the mean pain score reported was as high as 6.36 on a 10-point Likert Scale. The high intensity of their pain very much interfered with the daily activities of the participants. Pain interference was high and the participants had poor coping as indicated by the low pain self-efficacy. Depression and a low quality of life score was found. Upon completion of our PAP, there was a significant increase in pain self-efficacy, pain interference as well as quality of life for the participants in the experimental group and not in the control group, and this improvement sustained in 3-month follow up. The present study used a peer support models and proven to be effective in managing pain and pain related situations for nursing home residents with chronic pain. The peer volunteers involved in the pain management program taught relevant pain knowledge and pain management strategies to help our participants. Clinical Trial Registration:https://clinicaltrials.gov/ct2/show/NCT03823495, NCT03823495.